States, citizens and the privatisation of security - Krahmann, Elke (Cambridge University Press, 2010)
"Recent years have seen a growing role for private military contractors in national and international security. To understand the reasons for this, Elke Krahmann examines changing models of the state, the citizen, and the soldier in the UK, the US, and Germany. She focuses on both the national differences with regard to the outsourcing of military services to private companies and their specific consequences for the democratic control over the legitimate use of armed force. Tracing developments and debates from the late eighteenth century to the present, she explains the transition from the centralized warfare state of the Cold War era to the privatized and fragmented security governance, and the different national attitudes to the privatization of force. Details three country case studies, providing evidence for the key issues raised within the text. Each chapter includes a summary table to aid comparison between case studies and allow for easy reference. Provides proposals for the reform of civil-military relations"--Provided by publisher.